The photoface database - Zafeiriou,S; Hansen,M; Atkinson,G; Argyriou,V; Petrou,M; Smith,M; Smith,L (2011)
In this paper we present a new database suitable for both 2D and 3D face recognition based on photometric stereo, the so-called Photoface database. The Photoface database was collected using a custom-made four-source photometric stereo device that could be easily deployed in commercial settings. Unlike other publicly available databases the level of cooperation between subjects and the capture mechanism was minimal. The proposed device may also be used, to capture 3D expressive faces. Apart from the description of the device and the Photoface database, we present experiments from baseline face recognition and verification algorithms using albedo, normals and the recovered depth maps. Finally, we have conducted experiments in order to demonstrate how different methods in the pipeline of photometric stereo (i.e. normal field computation and depth map reconstruction methods) affect recognition/verification performance. © 2011 IEEE.